Anodic Behavior of Alloy 22 in Bicarbonate Media: Effect of Alloying. (2015) - Natalia, S. Zadorozne; Mabel, C. Giordano; Raúl, B. Rebak; Alicia, E. Ares; Ricardo, M. Carranza
Abstract: The alloy 22 (UNS N06022) is one of the candidates for the manufacture of containers of radioactive waste high level. These containers provide services in natural environments characterized by multi-ionic solutions, it is estimated they could suffer three types of deterioration: general corrosion, localized corrosion (specifically crevice) and stress corrosion cracking (SCC). It has been confirmed to produce cracking, requires the presence of bicarbonate and chloride ions. It has also determined that susceptibility to SCC could be related to the occurrence of an anodic peak in the polarization curves in these media to at potentials previous transpassive zone. The aim of this work is to study the anodic behavior of alloy 22 and its alloying effect in different media containing bicarbonate and chloride ions in different concentrations and temperatures. Polarization curves were made of alloy 22 (Ni-22% Cr-13% Mo), Ni-Mo (Ni-28, 5% Mo) and Ni-Cr (Ni-20% Cr) under the following conditions: 1mol/L NaCl at 90°C, and 1.148mol/L NaHCO3, 1.148mol/L NaHCO3 + 1 mol/L NaCl, 1.148mol/L NaHCO3 + 0.1mol/L NaCl at 90°C, 75°C, 60°C and 25°C. It was found that the alloy 22 has a current peak in the anodic at potential previous to transpassive zone, only when the medium has bicarbonate ions. Curves performed in 1 mol/L NaCl did not show any anodic peak, in any of the alloys tested. The curves made to alloys Ni-Mo and Ni-Cr in the media with bicarbonate ions, allowed to determine that Cr, is responsible for the appearance of the anodic peak in the Alloy 22. The curves of alloy B-3 showed no current peak in the conditions studied. The potential, at which the peak appears in the Alloy 22 and Ni-Cr alloy, increases with decreasing temperature. It also presents a variation of the peak with the composition of the solution. When the chloride ion is added to bicarbonate solution, the peak is shifted potential and higher current densities, depending on the concentration of added chloride ions.